PEDOMAN MEMILIH PEMIMPIN DALAM AL-QUR’AN (STUDI TAFSIR AL-AZHAR KARYA HAMKA) - Harahap, Asrim Muda; Siregar, Sawaluddin (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
This article is entitled Criteria for Leaders in the Al-Qur’an (Study of Tafsir Al-Azhar by Hamka), with the aim of knowing the verses on the criteria for leaders and what Hamka's Tafsir al-Azhar views on the verses on the criteria for leaders. This type of research is a library study, where the data obtained is in the form of written material. The primary data sources are the Al-Qur’an and Tafsir Al-Azhar. Meanwhile, relevant literature is used as a secondary source related to the research topic. Data collection was carried out using the maudhu'i method. The results of this research explain the criteria for leaders in the Qur'an, including those found in Q.S. Al-Ma'idah (5): 51, Q.S. Al-Anbiya' (21): 73, Q.S. Al-Baqarah (2): 247, Q.S. An-Nisa (4): 58 and Q.S. Yunus (10): 89.